2016
DOI: 10.1021/acssuschemeng.6b00420
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of Cellulose Using an Acidic and Hydrophobic Ionic Liquid and Subsequent Separation of Glucose Aqueous Solution from the Ionic Liquid and 5-(Hydroxymethyl)furfural

Abstract: Cellulose was hydrolyzed using a novel biphasic system consisting of water and an acidic and hydrophobic ionic liquid. The biphasic system enabled a simple separation of the resulting glucose aqueous solution and ionic liquid. Additionally, a fermentation inhibitor, 5-(hydroxymethyl)furfural, could be removed from the aqueous phase into the ionic liquid phase. The yield of glucose in cellulose hydrolysis was 12.9% at 190 °C. The distribution ratio of glucose in the aqueous phase was 0.98 with an ionic liquid/w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…Ionic liquids attract research interest; one of their interesting features is the ability to break down the intermolecular hydrogen bonds in cellulose and dissolve it. Properties of ionic liquids can be widely varied: for example, they can serve as an acid catalyst or facilitate enzymatic hydrolysis …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ionic liquids attract research interest; one of their interesting features is the ability to break down the intermolecular hydrogen bonds in cellulose and dissolve it. Properties of ionic liquids can be widely varied: for example, they can serve as an acid catalyst or facilitate enzymatic hydrolysis …”
Section: Introductionmentioning
confidence: 99%
“…[8] Ionic liquids attract research interest; one of their interesting features is the ability to break down the intermolecular hydrogen bonds in cellulose and dissolve it. Properties of ionic liquids can be widely varied: for example, they can serve as an acid catalyst [9] or facilitate enzymatic hydrolysis. [10] In 2008, possibility of cellulose hydrolysis with solid catalysts (sulfonated or oxidized carbons, ion exchange resins, zeolites, acidic oxide catalysts) was demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, Takahashi and co workers synthesized an acidic – hydrophobic IL comprising a long alkyl chain phosphonium cation and a HSO 4 − anion (trioctylpentylphosphonium hydrogensulfate) and performed the hydrolysis of cellulose. The recovery of glucose from the aqueous phase and separation of IL and HMF was possible by phase separation due to the significant polarity difference . The solvent extraction is another method under study for recovery of sugars from IL – biomass liquor .…”
Section: Recovery and Reuse Of Ionic Liquids Used For Biomass Processingmentioning
confidence: 99%
“…The recovery of glucose from the aqueous phase and separation of IL and HMF was possible by phase separation due to the significant polarity difference. [222] The solvent extraction is another method under study for recovery of sugars from IL -biomass liquor. [223] This solvent extraction technique is based on the chemical affinity of boronates such as phenylboronic acid and naphthalene-2boronic acid for sugars; which was applied to the extraction of glucose, xylose, and cellobiose from an aqueous solution of 1ethyl-3-methylimidazolium acetate.…”
Section: Ionic Liquid Catalyst(s)mentioning
confidence: 99%
“…Because of their remarkable capacity to delignify and solubilize cellulose, the ILs are often used for pretreating lignocellulosic biomass before hydrolysis [10][11][12][13][14][15]. On the other hand, Davis et al reported acidic ILs having an acidic group such as a sulfo group in their cationic and/or anionic structures [16][17][18][19][20], and the acidic ILs exhibit higher catalytic activity in cellulose hydrolysis compared to sulfuric acid [21].…”
Section: Introductionmentioning
confidence: 99%